Automatic generation of a Software Requirements Specification (SRS) document - Georgiades, Marinos G.; Andreou, Andreas S. (My University, 2010)
The lack of a software tool to automate the creation of a well-defined, Natural Language Software Requirements Specification (SRS) document is an obstacle to the process of efficient Requirements Engineering (RE). This paper provides an overview of a methodology and a novel software tool that attempt to formalize and automate the RE process, and it expands on the use of the SRS Documentation component of the tool that generates automatically a well-structured Natural Language SRS document. 2010 IEEE.
Keywords: Automated RE; Automated SRS; Automatic Generation; Natural languages; Software requirements specifications; Software tool; Computer software; Automation; Intelligent systems; Requirements engineering; Specifications; Systems analysis; Stimulated Raman scattering